2020
DOI: 10.1161/atvbaha.120.314491
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Restricts NETosis in Acute Mesenteric Ischemia-Reperfusion Injury

Abstract: Objective: Recruitment of neutrophils and formation of neutrophil extracellular traps (NETs) contribute to lethality in acute mesenteric infarction. To study the impact of the gut microbiota in acute mesenteric infarction, we used gnotobiotic mouse models to investigate whether gut commensals prime the reactivity of neutrophils towards formation of neutrophil extracellular traps (NETosis). Approach and Results: We applied a mesenteric isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…Remarkably, MAMPs derived from the gut microbiota can signal to distant vascular beds, influencing both endothelial cell function and platelet responses [ 18 , 19 , 20 ]. In the vasculature, remote signaling of microbial patterns is mediated by TLRs and nucleotide-binding oligomerization domain (NOD)-like receptors [ 15 , 21 ], impacting on hematopoiesis but also affecting the development of vascular disease states such as atherosclerosis, ischemia-reperfusion injury, and arterial thrombosis [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, MAMPs derived from the gut microbiota can signal to distant vascular beds, influencing both endothelial cell function and platelet responses [ 18 , 19 , 20 ]. In the vasculature, remote signaling of microbial patterns is mediated by TLRs and nucleotide-binding oligomerization domain (NOD)-like receptors [ 15 , 21 ], impacting on hematopoiesis but also affecting the development of vascular disease states such as atherosclerosis, ischemia-reperfusion injury, and arterial thrombosis [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since our gnotobiotic approach recently demonstrated a pro-adhesive role of a complex microbiota and of Escherichia coli JP313 and Bacillus subtilis PY79 in leukocyte adhesion in the mesenteric venules [ 44 ], we wondered whether the presence of the defined minimal microbial consortium ASF would impact on leukocyte adherence. Using high-speed fluorescence intravital microscopy, we observed a significantly reduced adhesion of leukocytes to the wall of mesenteric venules pre- and post-ischemia in ASF-colonized mice as compared to CONV-R mice that were colonized from birth with a complex gut microbiota ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Acute mesenteric infarction is characterized by a disrupted gut barrier and dysregulation of the host immune response [ 40 , 41 ]. It requires immediate treatment to prevent life-threatening complications, such as peritonitis and multiple organ failure [ 42 , 43 ]. In recent work with gnotobiotic mouse models, we revealed that the presence of gut microbiota enhances leukocyte adhesion to ischemia-reperfusion injured mesenteric venules, but efficiently suppresses the formation of neutrophil extracellular traps (NETs) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations